Kesiapan Pajak Karbon Indonesia dan Implementasinya Dalam Mewujudkan Sustainability Living - Fajarianti, Amalia Tri; Novitasari, Dewi Tri (JATIJAJAR LAW REVIEW, 2025)
Growing awareness of climate change and social justice is shifting people’s desires towards more sustainable and ethical choices. Indonesia is one of the world’s largest carbon emitters, grappling with rapid economic growth and environmental challenges. The country relies heavily on fossil fuels, which produce greenhouse gas emissions from coal-fired power plants. Rising global temperatures illustrate the urgent need for climate action, exemplified by the Paris Agreement, which aims to limit warming to 1.5-2 degrees Celsius. To combat climate change, countries must transform their economies and policies. Indonesia’s commitments include targets to significantly reduce greenhouse gas emissions by 2030 and achieve net-zero emissions by 2060. The implementation of a carbon tax, as part of the Tax Regulation Harmonization Law, is critical in curbing emissions. A carbon tax creates financial incentives for businesses and individuals to adopt sustainable practices and invest in renewable energy. This study uses qualitative normative legal analysis to evaluate the effectiveness of Indonesia’s carbon tax policy by emphasizing the principle of sustainability. Ultimately, the implementation of a carbon tax not only aims to reduce emissions but also encourages sustainable living while aligning with international climate agreements and sustainable development goals.